Bilateral Trade Balance of Malaysia to the United States, Japan and Singapore: Empirical Evidence from the Monetary Approach - Wong Hock Tse (2008)
This study examines the long-run and short-run impact of real exchange rate onbilateral trade balance of Malaysia to the United States (US), Japan and Singaporeusing an augmented model of Rose and Yellen (1989). In the long run, depreciationor devaluation of real exchange rate will generally improve bilateral trade balance.However, the impact of real exchange rate on bilateral trade balance is differentacross countries in the short run. Moreover, changes in money supply could have animpact on real exchange rate and therefore, bilateral trade balance. Thus, monetarypolicy could be an effective policy on trade with other countries.